Non-verbal communication in the workplace: Perceptions of hospitality management Filipino student interns in the service encounters - Malate, Justin Joyce; Garcia, Czar Evans Philip; Granados, Eric Luis; Lor, Heaven Kage; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
Effective communication plays a crucial role in the hospitality industry's successful service encounter. Although verbal communication is significant for this role, non-verbal communication is just as significant. However, there's a relatively limited body of knowledge about non-verbal communication in the hospitality and tourism literature. Therefore, the study's objectives are to elucidate the perception of Filipino hospitality management student interns of the roles of non-verbal communication and how its dimensions assist in the service encounters. By achieving the abovementioned objectives, the findings have provided valuable insights to the inadequate knowledge. Using a qualitative approach, specifically interpretative phenomenological analysis (IPA), target students from Bachelor of Science in Hospitality Management (BSHM) taking an internship in Tacloban City. Applying purposive convenience sampling, 18 selected participants who conformed to the criteria were interviewed (semi-structured). The data collected were analyzed using Braun and Clarke's (2021) thematic analysis, followed by Saldaña's (2015) manual coding for the emergence of themes imperative for final conclusions. Findings show that non-verbal communication is an important part of service encounters, promoting effective connections, improving customer satisfaction, and optimizing customer interaction. While the non-verbal dimensions including facial expressions, kinesics, paralinguistics, and proxemics greatly aids by creating exceptional customer experiences and enhancing overall service quality. While the student interns met the customer's demands and forged stronger bonds by effectively utilizing and understanding these non-verbal cues. Therefore, it concludes that non-verbal communication intervention and the assistance provided by its dimensions contribute to successful service encounters and create favorable experiences for both student interns and customers.